Inhibition of Notch Signaling Promotes the Differentiation of Epicardial Progenitor Cells into Adipocytes. (9th April 2021) - Liu, Bin; Wang, Dinghui; Xiong, Tianhua; Liu, Yajie; Jing, Xiaodong; Du, Jianlin; She, Qiang
Abstract : Background . The role of Notch signaling pathway in the differentiation of epicardial progenitor cells (EPCs) into adipocytes is unclear. The objective is to investigate the effects of Notch signaling on the differentiation of EPCs into adipocytes. Methods . Frozen sections of C57BL/6 J mouse hearts were used to observe epicardial adipose tissue (EAT), and genetic lineage methods were used to trace EPCs. EPCs were cultured in adipogenic induction medium with Notch ligand jagged-1 or γ -secretase inhibitor DAPT. The adipocyte markers, Notch signaling, and adipogenesis transcription factors were determined. Results . There was EAT located at the atrial–ventricular groove in mouse. By using genetic lineage tracing methods, we found that EPCs were a source of epicardial adipocytes. EPCs had lipid droplet accumulation, and the expression of adipocyte markers FABP-4 and perilipin-1 was upregulated under adipogenic induction. Activating the Notch signaling with jagged-1 attenuated the adipogenic differentiation of EPCs and downregulated the key adipogenesis transcription factor peroxisome proliferator activated receptor- γ (PPAR- γ ), while inhibiting the signaling promoted adipogenic differentiation and upregulated PPAR- γ . When blocking PPAR- γ, the role of Notch signaling in promoting adipogenic differentiation was inhibited. Conclusions . EPCs are a source of epicardial adipocytes. Downregulation of the Notch signaling pathway promotes the differentiation of EPCs into adipocytes via PPAR- γ .